Participatory Design for Enhancing the Shopping Experience - Yao, Xinyun (My University, 2013)
Shopping experiences have become an important factor for the competitive retail industry, and they can be enhanced by technology. Technology allows the in-store experiences to be digitally enhanced. Existing applications focus on improving the connections between customers and products. Technology can help construct relations between tangible in-store shopping and virtual experiences beyond shopping. By involving customers and stakeholders in the early stage of design, the connections of digital and tangible shopping can be explored to enhance the shopping experience. This participatory design methodology provides an approach for innovating interactive shopping experiences. The thesis explores spaces for an interactive in-store shopping experience through participatory design methodology. The main discussion of the thesis is around how the design methods support the articulation of shopping experience innovation. The innovation project in the report aims at enhancing and enriching the shopping experience for female fashion retailers. Through the innovation project, various methods of participatory design are analysed. This includes the ethnographic studies and co-creational strategies in workshops. While ethnographic studies of customers expand knowledge for innovation, co-creation develops concepts to fulfil the customer’s requirements and brand’s vision. Through the iteration of methods and design with a participatory approach, novel experiences are generated. This thesis results in a concept as an exemplification of the methodology implementation, and concludes with a synthesis of methods that can be applied in the area.
Keywords: Annan teknik; Interaktionsteknik; Other Engineering and Technologies; Interaction Technologies